DAMPAK KONSERVATISMA TERHADAP RELEVANSI NILAI INFORMASI AKUNTANSI DI INDONESIA - , Darsono, SE.MBA.Akt. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study examines the relationship of intrinsic value to the company's market value. Company's intrinsic value is reflected in the financial statement numbers, while the company's market value is reflected in the stock price. Its association indicates the value relevance of accounting information. The results of previous studies showing a decline in the value relevance of accounting information when its value is very low (Lev, 1989